Local News and Municipal Elections in the Czech Republic : Do Publicly funded Newsletters help Incumbents to win Elections? - Boháček, Jiří; Bertoli, Paola; Dušek, Libor; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
In the Czech Republic, town halls are allowed to issue printed newspapers to inform the residents about local events. The newspapers are funded from municipal budgets and free for the residents, often delivered directly to the mailbox. Apart from being useful source of information, the newspapers may serve also as a platform for election campaign of the incumbent politicians. This fact was the main reason for the amendment of the Press Act in 2013, directing municipalities to issue unbiased news with enough room for all the political stakeholders. The present study uses various secondary data to examine the effects of town hall newspapers on voting decisions during municipal elections held between 1998 and 2014. Econometric analysis finds significant and positive relationship between presence of a newspaper and performance of incumbent politicians. Comparison of election results from 2014 with previous election years suggest that the Press Act amendment has not had substantial impact on this relationship.
Vedoucí práce: Paola Bertoli
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses